Lithocholic Acid Hydroxyamide Destabilizes Cyclin D1 and Induces G0/G1 Arrest by Inhibiting Deubiquitinase USP2a. Issue 4 (20th April 2017) - Magiera, Katarzyna; Tomala, Marcin; Kubica, Katarzyna; De Cesare, Virginia; Trost, Matthias; Zieba, Bartosz J.; Kachamakova-Trojanowska, Neli; Les, Marcin; Dubin, Grzegorz; Holak, Tad A.; Skalniak, Lukasz
Summary: USP2a is a deubiquitinase responsible for stabilization of cyclin D1, a crucial regulator of cell-cycle progression and a proto-oncoprotein overexpressed in numerous cancer types. Here we report that lithocholic acid (LCA) derivatives are inhibitors of USP proteins, including USP2a. The most potent LCA derivative, LCA hydroxyamide (LCAHA), inhibits USP2a, leading to a significant Akt/GSK3β-independent destabilization of cyclin D1, but does not change the expression of p27. This leads to the defects in cell-cycle progression. As a result, LCAHA inhibits the growth of cyclin D1-expressing, but not cyclin D1-negative cells, independently of the p53 status. We show that LCA derivatives may be considered as future therapeutics for the treatment of cyclin D1-addicted p53-expressing and p53-defective cancer types. Graphical Abstract: Highlights: Lithocholic acid (LCA) derivatives are inhibitors of USP proteins in vitro LCA hydroxyamide (LCAHA) inhibits USP2a, leading to destabilization of cyclin D1 LCAHA inhibits growth of cyclin D1-dependent cells at submicromolar concentrations Growth-inhibitory activity of LCAHA is independent of p53 status Abstract : Magiera et al. demonstrate that the lithocholic acid (LCA) derivative, LCAHA, inhibits deubiquitinase USP2a. This leads to destabilization of cyclin D1 and growth inhibition of cyclin D1-dependent cells at submicromolar concentrations. The activity of LCAHA is independent of p53 status.